(untitled) (Experimental biology, 2022)
Ribosomal protein S6 (RPS6) is a component of eukaryotic 40S ribosomal subunits (40S-RSu) that regulates the translation of certain types of mRNA. RPS6 is the unique 40S-RSu protein which is able to phosphorylation, it is one of the targets for the regulation of protein biosynthesis in eukaryotes. There is evidence that ribosomes with the highest level of phosphorylation of RPS6 create selective advantages in translation of mRNAs encoding a lot of the protein components of the cell translational apparatus. Understanding the mechanism of regulation of plant biosynthesis through phosphorylation of pRPS6 will increase plant biomass and yield. In this work, the AtRPS6A1 cDNA gene encoding the ribosomal protein S6, was cloned into the pET19b vector. This gene is expressed in Escherichia coli cells, and the recombinant PRS6 protein encoded by it is isolated by ion and affinity (IMAC) chromatography, purified by dialysis and concentrated. The PRS6 protein will be used in in vitro experiments to study the molecular mechanisms of regulation of plant mRNA translation through its phosphorylation and production of monoclonal antibodies to this protein.